Pengaruh Profitabilitas, Leverage, dan Ukuran Perusahaan Terhadap Audit Delay Pada Saat Pandemi dan Era New Normal (Studi Empiris Pada Perusahaan Healthcare Yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022) - Clara Valencia; Kurnia Indah Sumunar (International Forum of Researchers and Lecturers, 2023)
This study examines Heatlhcare companies listed on the Indonesia Stock Exchange. This study aims to determine the effect of Profitability, Leverage, and Company Size on Audit delay experienced by healthcare companies during the pandemic and the new normal era. The sample companies are 19 healthcare companies on the IDX. The dependent variable used is audit delay and the independent variables used include: Profitability, Leverage, and Firm Size. The analysis of this study uses multiple linear regression with SPSS 25 (Statistical Package for Social Science). The results of this study indicate that: (a) Profitability has an effect on audit delay; (b) Leverage has no effect on audit delay; (c) Company size has no effect on audit delay; (d) Simultaneously the independent variables affect the dependent variable.